LARANGAN PELAKSANAAN PERKAWINAN PEGITON (BERBEDA SUKU) DI DESA KEPAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Weni Hartanti; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Marriage is abond physical and mentally between a man and woman as husband and wife with the aim of forming a family or household that is happy and enternally based on God . Not all marriages can occur, even though the marriage fulfills all the pillars and stipulated conditions. As well as a ban on native tribes between marriages in Kepau Jaya Village, Siak HuluSub-District, Kampar District. Most customary prohibitions in the Kampar District area prohibit the marriage of my ancestors because they adhere to the exogamy system but in the village of Kepau Jaya not only prohibits the marriage of my family but there is also a marriage ban for Pegiton due to prohibited vows. Problems in this thesis, namely: First, What is the reason for the prohibition of Pegiton Marriage (different ethnic groups) in the Kepau Jaya Village, Siak Hulu Sub-District, Kampar District? second, what are the factors causing the implementation of Pegiton Marriage (different ethnic groups) in the Kepau Jaya Village, Siak Hulu District, Kampar Regency?This type of research can be classified into a type of sociological juridical research, because the author directly conducts research on the location or point being examined to provide a complete and clear picture of the problem being examined. This research was conducted in Kepau Jaya Village, Siak Hulu Subdistrict, Kampar District, while the sample population was all parties related to the problems examined in this study, data sources used, primary data and secondary data, data collection techniques in this study with interviews and literature studies.From the research, there are two things that can be concluded first. The causal factor is why the pegiton marriage is banned in Kepau Jaya Village, Siak Hulu District, Kampar Regency. Second, the causes of the implementation of the ban on marriage of pegiton in the present.Keywords: Prohibition of Indigenous Marriage - Kepau Jaya Village